An Examination of the use of computer-based formative assessments - Sullivan, Patrick; McBrayer, Juliann Sergi; Miller, Suzanne; Fallon, Katherine (Computers and education, 2021)
The purpose of this quantitative, correlational study was to investigate the computer-based formative assessment (CBFA) practices of core academic teachers within a one-to-one computing environment to better understand the relationships between CBFA usage rates of teachers and their perceptions of instructional technology. Survey data were collected from 261 academic teachers (63% response rate), which quantified teacher CBFA usage rates. The major findings of the study indicated that there were statistically significant correlations between CBFA usage rates and teacher comfort with technology, teacher belief in technology, and teacher autonomy. Significant differences in CBFA usage rates were found between different subjects, class levels, and grade levels. The findings provide insight into how teachers utilize CBFA in their classrooms to aid in developing targeted professional development to support teachers in using technology to formatively assess students. Future research into the effectiveness of increased CBFA usage could demonstrate how student achievement may be related to increased use of this instructional tool. •Significant correlations between CBFA usage rates and teacher comfort with technology, belief in technology, and autonomy.•Significant differences in CBFA usage rates were found between different subjects, class levels, and grade levels.•Teachers using CBFA could advance of professional development to support using technology to formatively assess students.•Increased CBFA usage on student achievement could further display how achievement may be related to increased use of CBFA.